Gempur Sehati (Gerakan Masyarakat Peduli Remaja Sehat Reproduksi) - Nuraini Putri , Valendira; Izza , Rosyadatul; Valensia Sam , Ahwalia (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Gempur Sehati (Gerakan Masyarakat Peduli Remaja Sehat Reproduksi) is a socialization program for parents and adolescents regarding reproductive health and effective communication between parents and children. Parents have a very important role in the growth of children, especially when children become teenagers, one of which is in terms of reproductive health knowledge. Providing reproductive health knowledge to children must be done early in order to avoid adverse impacts such as early marriage which can lead to health problems such as Sexually Transmitted Diseases, LBW (Low Birth Weight) and stunting. Objective : This program aims to increase parents' awareness of the importance of communication between parents and children regarding reproductive health and increase knowledge in adolescents. Research Methods/ Implementation Methods : The population and samples taken were the community of Kelurahan Sepaku RT 01, 02, 03, 04, and 05 as many as 110 families. This research design uses quantitative with a cross-sectional approach. The sampling technique used purposive sampling technique by collecting data in the form of observations, questionnaires, and interviews. Results : From the results of the data obtained from the questionnaire, it is known that the low knowledge of adolescent reproductive health in the Kelurahan Sepaku area, therefore the Gempur Sehati activity was carried out. The program was attended by 23 people with 17 parents and 6 teenagers. From the results of the pre-test and post-test of this activity, a p-value of 0.093> 0.05 was obtained. Conclusion/Lesson Learned : Indicating that there was no significant difference between the two activities.